Suppression of chemotherapy-induced cytokine/lipid mediator surge and ovarian cancer by a dual COX-2/sEH inhibitor - Gartung, Allison (Proc Natl Acad Sci U S A, 2019)
Although chemotherapy is a conventional cancer treatment, it may induce a protumorigenic microenvironment by triggering the release of proinflammatory mediators. In this study, we demonstrate that ovarian tumor cell debris generated by first-line platinum- and taxane-based chemotherapy accelerates tumor progression by stimulating a macrophage-derived “surge” of proinflammatory cytokines and bioactive lipids. Thus, targeting a single inflammatory mediator or pathway is unlikely to prevent therapy-induced tumor progression. Here, we show that combined pharmacological abrogation of the cyclooxygenase-2 (COX-2) and soluble epoxide hydrolase (sEH) pathways prevented the debris-induced surge of both cytokines and lipid mediators by macrophages. In animal models, the dual COX-2/sEH inhibitor PTUPB delayed the onset of debris-stimulated ovarian tumor growth and ascites leading to sustained survival over 120 days postinjection. Therefore, dual inhibition of COX-2/sEH may be an approach to suppress debris-stimulated ovarian tumor growth by preventing the therapy-induced surge of cytokines and lipid mediators.